Chemically induced degradation of CDK9 by a proteolysis targeting chimera (PROTAC). Issue 54 (21st June 2017) - Robb, Caroline M.; Contreras, Jacob I.; Kour, Smit; Taylor, Margaret A.; Abid, Mohammad; Sonawane, Yogesh A.; Zahid, Muhammad; Murry, Daryl J.; Natarajan, Amarnath; Rana, Sandeep
Abstract : In this manuscript, for the first time, we report the synthesis of a PROTAC that selectively degrades cyclin dependent kinase 9 (CDK9). Abstract : Cyclin-dependent kinase 9 (CDK9), a member of the cyclin-dependent protein kinase (CDK) family, is involved in transcriptional elongation of several target genes. CDK9 is ubiquitously expressed and has been shown to contribute to a variety of malignancies such as pancreatic, prostate and breast cancers. Here we report the development of a heterobifunctional small molecule proteolysis targeting chimera (PROTAC) capable of cereblon (CRBN) mediated proteasomal degradation of CDK9. In HCT116 cells, it selectively degrades CDK9 while sparing other CDK family members. This is the first example of a PROTAC that selectively degrades CDK9.